Analisis Perhitungan Stabilitas Lereng dengan Metode Fellenius (Ordinary Method of Slice) Menggunakan Program PHP (Professional Home Page Hypertext Preprocessor) - Fatria, Akhmad Ridho; Iswan, Iswan; Zakaria, Ahmad (Universitas Lampung, 2016)
Slopes as we know is a sloping ground surface and forming an angle to a horizontal plane andunprotected. Slopes there are generally divided into two categories of land slope, the naturalslopes and artificial slopes. Slope collapse could occur as a result of thrust arising due to the loadon the ground. In the method of calculation of the safety factor of the slope stability, a methodfrequently used in calculating the slope stability is by Fellenius method (Ordinary Method ofSlice), Fellenius method first introduced by Fellenius, slope stability calculations with Felleniusmethod if the count is use a lot of complicated manual calculations so that it becomes lesspractical and relatively take times.One effort to get the accurate calculation of slope stability in a short time, which is by making thesafety factor calculation program on the stability of the slope using a programming language.From the comparison calculation with the program and the results of manual counting,Calculating the percentage difference of less than 1 %, so the program can be used. With the datathat you have this program is able to calculate with no more than 1 minute after entering the dataslope previously calculated manually. While for the time that is required in calculating or writingthe result of manual calculation takes more than 60 minutes. Then it will produce time efficiencyfaster than using a manual calculation.Keywords: Analysis of Slope Stability, Safety Factor, Fellenius Method, PHP